Diagnosis of AML Due to Sudden Onset Hearing Loss - Kumu, Shahreen Fatema; Salam, Abdus; Jaman, Nadia; Chowdhury, Md Shahabul Huda (Journal of Medicine, 2025)
A male patient of 24 years old presented with bilateral hearing loss for 15 days, which was associated with headache and dizziness. Another complaint was two episodes of hemoptysis and a single episode of haematemesis a week back. On examination, the patient was found severely anaemic, with vitals within normal range; no organomegaly or lymphadenopathy was found. Microscopic examination of the ear revealed bilateral hemotympanum, and Pure Tone Audiometry showed moderate to severe conductive hearing loss in both ears. The department of ENT suggested Conservative management, and in case of an inadequate treatment response, myringotomy was advised as a further course of action. The patient responded well to the former one. Meanwhile, in routine laboratory investigations, hemoglobin was found to be very low (Hb: 3 mg/dL) with a high number of blast cells (85%) in the peripheral blood film. A bone marrow study and other relevant investigations suggested by hematology confirmed the diagnosis of Acute Myeloid Leukemia (AML), which prompted the initiation of guideline-based treatment. J MEDICINE 2025; 26(2): 173